Implementasi Word Of Mouth Marketing di Era Digital Pada PT. ZUZU Teknologi Servis (Zuzu Hospitality) - Mahdy Alief Setiawan (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2023)
Zuzu Hospitality is a Software as a Service (SaaS) service that helps hotel owners manage operations, market rooms on various Online Travel Agent (OTA) sites, and manage income. The research entitled "Implementation of Word Of Mouth Marketing at PT. ZUZU Service Technology (Zuzu Hospitality)" aims to find out how Zuzu Hospitality implements its marketing communications using Word Of Mouth Marketing in this digital era. The theory used in this research is the theory from Sernovitz, where this research uses a qualitative descriptive method. with data collection techniques using structured interviews and observation and assisted with supporting documentation as complementary evidence. Then the data that has been obtained and collected in a comprehensive manner is then analyzed in a way, namely data reduction, data presentation, and making summary sheets. From the process of the research stages that were carried out, the results of the research can be analyzed that Word Of Mouth Marketing carried out by Zuzu Hospitality is based on Talking, Topics, Tools, Talking Part, and Tracking. The results of these several elements provide that Talkers from Zuzu Hospitality in carrying out W The OM is the Sales team. Then the sales team will explain what are the benefits of joining Zuzu and what benefits will be obtained monthly or annually, this refers to the Topics that are part of the WOM element. Meanwhile, Tools use CRM, Slack, Telegram, Whatsapp, Zoom, and Google Meet. For Talking Part, there are CM (Commercial Manager), PS (Partner Support), PD (Partner Development), and PIC Hotel who have signed with Zuzu to help in running this Word Of Mouth Marketing. Finally, there is tracking carried out by the CM or Sales Senior to monitor whether the WOM implementation is appropriate or not satisfactory enough for the company. Then this research can be implemented for marketing communication strategies in increasing sales and influencing target segmentation.